STUDY OF THE IMPACT OF CHRONIC SLEEP DISORDERS ON THE IMMUNE SYSTEM AND ITS DIAGNOSTIC CRITERIA (International journal of medical sciences, 2025)
Sleep is one of the most essential physiological processes ensuring the homeostatic stability of the human body. It plays a crucial role in the optimal functioning of the central nervous system, endocrine system, immune system, and metabolic pathways. Prolonged sleep deprivation acts as a significant stress factor on the body’s major homeostatic systems. Insufficient sleep enhances systemic inflammation through activation of the hypothalamic–pituitary–adrenal (HPA) axis, continuous stimulation of the sympatho-adrenal system, and disruption of cytokine balance.